An Efficient Route to Rapidly Access Silica Materials with Differently Ordered Mesostructures through Counteranion Exchange. Issue 31 (20th June 2013) - Lin, Changxu; Zhu, Wei; Li, Jian; Liu, Xiyang; Li, Weina; Jiang, Yin; Yang, Haowei; Li, Guangtao
<x xml:space="preserve">Abstract</x> Control via exchange: By using a new type of imidazolium‐based gemini surfactant as the template, highly ordered cubic mesoporous silica material (MCM‐48) was directly synthesized in a broad range of reactant compositions and under mild conditions (see scheme). Moreover, by a simple counterion exchange strategy, hexagonal (MCM‐41) and lamellar (MCM‐50) mesoporous silicas are also easily and efficiently accessible.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>